Changes in the paravertebral muscles in patients with degenerative diseases of the lumbar spine - Radchenko, Volodymyr; Skidanov, Artem (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Studying of changes in paravertebral muscles is necessary for understanding the prognosis of the course, developing strategies for the prevention and treatment of patients with degenerative diseases of the spine. Objective: to determine changes in paravertebral muscles in patients with degenerative diseases of the lumbar spine. Methods: 129 patients who were operated on the reason of instability, intervertebral disc hernias, spondylolisthesis, spinal stenosis, and 11 healthy volunteers were examined on a spiral computer tomograph SOMATOM Emotion. The content of fat, muscle and connective tissues in the paravertebral muscles was determined with the help of an original computer program. A correlation analysis for the assessment was performed. Results: in patients with intervertebral discs hernias, spondylolisthesis and stenosis of the vertebral canal, the fat content in the paravertebral muscles was higher than in the control group (7.24 ± 1.56) and (16.03 ± 1.62); (18.40 ± 2.17) and (19.70 ± 2.36) % relatively. The differences were more pronounced in m. multifidus and m. erector spinae. A significant decrease in the amount of muscle tissue was observed in patients with s pondylolisthesis (M–W U = 95, Z = –2.51082, p = 0.01) and stenosis (M–W U = 39, p = 0.007). The most pronounced changes, as in the case of fat tissue, were found in m. erector spine and m. multifidus. The content of connective tissue in groups with herniated intervertebral discs, spondylolisthesis and spinal stenosis did not differ from the control parameters, and in patients with instability its quantity was significantly higher. Conclusions: degenerative changes in the muscles directly correlate with disorders of other structures of the spine and progress depending on the diagnosis in the order: «instability – herniated intervertebral disc – spondylolisthesis – stenosis of the spinal canal».